Syntactic comprehension deficits in Alzheimer's disease - Bickel, Claudia; Pantel, Johannes; Eysenbach, Katrin; Schröder, Johannes (Brain and language, 2002)
Syntactic comprehension of German patients with dementia of the Alzheimer type was investigated and compared to healthy controls matched with respect to age, sex, and education. Special attention was directed at syntactic structures, which, in contrast to a language like English, are feasible in a grammatically rich language like German. In a sentence picture matching paradigm, only semantically reversible sentences were used. Syntactic complexity ranged from simple active voice sentences to more complex sentences like center-embedded object relative sentences. In comparison to their controls, patients showed a deficit in nearly all categories. Their performance was not influenced by age, but was heavily influenced by the degree of cognitive impairment. Patients with mild cognitive impairment, as defined by a MMSE score of 20 or higher, showed only slight difficulties in syntactic processing, whereas patients with moderate to severe impairment (MMSE < 20) did not perform above chance limits in most syntactic categories. It appears as though syntactic comprehension is only mildly affected in the early stages of Alzheimer's disease and is rather severely impaired in more advanced stages. In the present report, results are discussed in terms of working memory demands for syntactic processing.